Kinetic Regularity of the Formation of Fe(II)–Fe(III) LDH Structures (Green Rust) on the Steel Surface in Presence of the FeSO4 and Fe2(SO4)3 Water Solutions - Lavrynenko, O.M.; Korol, Ya.D.; Netreba, S.V.; Prokopenko, V.A. (Хімія, фізика та технологія поверхні, 2010)
The kinetic regularity of origin and transformation of the Fe (II)–Fe (III) LDH structures on the steel electrodes surface contacting with FeSO4 and Fe2(SO4)3 dispersion medium at free access of the air oxygen into the system was studied. X-ray diffraction was chosen as the main method of investigation. It was shown that regardless of oxidation level of iron with its concentration 102–103 mg/dm3 on electrode surface the GR(SO4 2-) phase was formed staying single for almost 5 hours. The phase transformation of embryonic GR(SO4 2-) surface structures occur with formation of morphological composites of iron-oxygen g -row: lepidocrocite g -FeOOH and magnetite Fe3O4, and α-row structure representative, goethite α-FeOOH. Досліджені кінетичні закономірності зародження та перетворення структур Fe (II)–Fe (III) шаруватих подвійних гідроксидів (ШПГ) на поверхні сталевого електрода, який контактує з дисперсійним середовищем, що містить FeSO4 та Fe2(SO4)3, за умови вільного надходження в систему кисню повітря. Головним методом дослідження був рентгенофазовий аналіз (РФА). Показано, що незалежно від ступеня окиснення заліза в дисперсійному середовищі при його концентрації 102–103 мг/дм3 на поверхні електроду утворюється фаза GR(SO4 2-), яка залишається єдиною протягом 5 годин. Фазові трансформації зародкових поверхневих структур GR(SO4 2-) проходять з утворенням залізокисневих структур g -ряду: лепідокрокіту g -FeOOH і магнетиту Fe3O4 та представника α-ряду, гетиту α-FeOOH. Исследованы кинетические закономерности зарождения и трансформации структур Fe (II)-Fe (III) слоевых двойных гидроксидов (СДГ) на поверхности стального электрода, который контактирует с дисперсионной средой, содержащей FeSO4 и Fe2(SO4)3, при свободном доступе в систему кислорода воздуха. Основным методом исследования был рентгенофазовый анализ (РФА). Показано, что независимо от степени окисления железа в дисперсионной среде при его концентрации 102–103 мг/дм3 на поверхности электрода образуется фаза GR(SO4 2-), которая остается единственной в течение 5 часов. Фазовые трансформации зародышевых поверхностных структур GR(SO4 2-) проходят с образованием железо-кислородных структур γ-ряда: лепидокрокита γ-FeOOH и магнетита Fe3O4 и представителя α-ряда, гетита α-FeOOH.